People, parasites, and plowshares : learning from our body's most terrifying invaders - Despommier, Dickson D. (New York : Columbia University Press, 2013)
An account of the biology, behavior, and history of parasites, following the interplay between these fascinating life forms and human society over thousands of years. Despommier focuses on long-term host-parasite associations, which have evolved to avoid or even subvert the human immune system.
This new house : Trichinella spiralis -- Hooked on parasites : Ancylostoma duodenale and Necator americanus -- Houdini's nefarious cousins : the trypanosomes, the schistosomes, and the lymphatic filariae -- A parasite for all seasons : Toxoplasma gondii -- The unholy trinity : Ascaris lumbricoides, Trichuris trichiura, and the hookworms -- The long and the short of it : tapeworms - Taenia saginata, Taenia solium, Diphyllobothrium latum, Echinococcus granulosus, and Echinococcus multilocularis -- All's well that ends well : Dracunculus medinensis -- Nature has all the answers. What's your question?.
Includes bibliographical references (pages [199]-201) and index.
Keywords: Parasites -- Popular works; Host-parasite relationships -- Popular works; Medical parasitology -- Popular works; Parasitology